2018
DOI: 10.1007/s00246-017-1802-7
|View full text |Cite
|
Sign up to set email alerts
|

Remote Ischemic Preconditioning has a Cardioprotective Effect in Children in the Early Postoperative Phase: A Meta-Analysis of Randomized Controlled Trials

Abstract: In this updated meta-analysis, we assessed the cardioprotective effect of remote ischemic preconditioning (RIPC) in pediatric patients undergoing congenital heart surgery. A total of 9 randomized controlled trials (RCTs) involving 793 pediatric patients under 18 years old were identified. RIPC obviously reduced the release of troponin I at 6 h after surgery [standard mean difference (SMD) -0.59, 95% confidence interval (CI) -1.14 to -0.04; p = 0.03], mitigated the inotropic scores within 4-6 h (SMD -0.43, 95% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…Likewise, Min et al reported that RIPC reduced the incidence of MV > 48 hours after cardiac surgery. 8 Similarly to past studies 70,71 , the present analysis showed that RIPC was associated with a slightly shorter duration of MV (1 hour). Our analysis also showed high heterogeneity (I 2 = 84%), which was not explained by a sub-group analysis strati ed by age or anesthetic regimen.…”
Section: Discussionsupporting
confidence: 85%
“…Likewise, Min et al reported that RIPC reduced the incidence of MV > 48 hours after cardiac surgery. 8 Similarly to past studies 70,71 , the present analysis showed that RIPC was associated with a slightly shorter duration of MV (1 hour). Our analysis also showed high heterogeneity (I 2 = 84%), which was not explained by a sub-group analysis strati ed by age or anesthetic regimen.…”
Section: Discussionsupporting
confidence: 85%
“…A meta-analysis suggested that RIPC reduces myocardial injury during cardiac surgery [32], but subsequently two large multi-centre trials in adults failed to show benefit in either composite cardiovascular endpoints or troponin release [30,31]; both were criticised for using propofol anaesthesia after it had been shown to interfere with the preconditioning pathway [16,17]. In a more recent meta-analysis in children, including 793 patients in 9 trials, Tan et al determined that RIPC has a cardioprotective effect, with reduced troponin release at 6 hours, lower inotrope scores in the first 12 hours, and reduced PICU stay following surgery [33]; however they were unable to include the only large trial in most analyses due to a lack of suitable published data. Our trial makes an important contribution to the literature, raising significant doubts about the use of RIPC in paediatric cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, RIPC attenuated ischemia-reperfusion-induced rise in LDH-1 and cTnT and decline in LVDP, which suggests its cardioprotective effects. RIPC has been shown to produce immediate as well as delayed cardioprotective effects 20 , 21 . In this study, the delayed cardioprotective effects of RIPC were assessed and the present study results were similar to previously published reports on RIPC 22 .…”
Section: Discussionmentioning
confidence: 99%